Strategi Psikopedagogis dalam Mengatasi "Short Attention Span” pada Anak Usia Sekolah Dasar Akibat Konsumsi Konten Digital Singkat - Balqis, Rizqiyah Ratu; Syaikhu, Ach.; Nisa, Khoirotun; Maulidia Afriani, Dinina (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The development of digital technology has brought about major changes in the information consumption patterns of elementary school-aged children. Platforms such as TikTok, YouTube Shorts and Instagram Reels provide short-form video content that is dense with visual and audio stimuli, but have the effect of decreasing children's attention span in the learning process. This short attention span phenomenon is a serious challenge in the world of basic education. This study aims to examine psychopedagogical strategies that can be applied to overcome concentration disorders in children due to the consumption of short digital content. This research uses a qualitative approach with a literature study method, which examines a number of scientific articles from various national and international databases. The results of the study show that children who habitually consume instant videos show decreased focus, difficulty completing long-term tasks, and decreased learning perseverance. In response, psychopedagogical strategies identified include mindfulness-based learning, reflective learning, project-based learning, and integration of local and spiritual values. These strategies not only stimulate concentration, but also shape children's character to be resilient in the face of instant culture. This research recommends the need for collaboration between teachers and parents, as well as the development of contextual learning modules to answer this challenge. Psychopedagogical strategies can be an applicable integrative solution in shaping a healthy learning culture in the digital era